Dispersion and Stabilization of Exfoliated Graphene in Ionic Liquids - Bordes, Emilie; Morcos, Bishoy; Bourgogne, David; Andanson, Jean-Michel; Bussière, Pierre-Olivier; Santini, Catherine C.; Benayad, Anass; Costa Gomes, Margarida; Pádua, Agílio A. H. (Frontiers in Chemistry, 2019)
The liquid-phase exfoliation of graphite is one of the most promising methods to increase production and commercial availability of graphene. Because ionic liquids can be easily obtained with chosen molecular structures and tuneable physicochemical properties, they can be use as media to optimise the exfoliation of graphite. The under- standing of the interactions involved between graphite and various chemical functions in the solvent ions will be helpful to find liquids capable of dissociating and stabilising im- portant quantities of large graphene layers. After a step of sonication, as a mechanical precursor, samples of suspended exfoliated graphene in different ionic liquids have been characterised experimentally in terms of flake size, number of layers, total concentration and purity of the exfoliated material. Nine different ionic liquids based on imida- zolium, pyrrolidinium and ammonium cations and on bis(trifluoromethylsulfonyl)imide, triflate, dicyanamide, tricyanomethanide, and methyl sulfate anions have been tested. UV-vis, Raman, X-ray photoelectron and electrochemical impedance spectroscopy in addition to high resolution transmission electron and atomic force microscopy have been selected to characterise suspended exfoliated graphene in ionic liquids. The num- ber of layers in the flakes exfoliated, the size and concentration depend of the structure of the ionic liquid selected. In order to obtain large flake sizes, ionic liquids with bis(trifluoromethylsulfonyl)imide anions and a cation with an alkyl chain of medium length should be selected. Smaller cation and anion favours the exfoliation of graphene. The exfoliation caused the formation of C-H bonds and the oxidation of the graphitic surface.